Semi-open urban blocks and convertible apartments: A–4 residential buildings in Novi Sad, awarded the Borba prize for architecture - Antešević, Nebojša; Gubić, Ilija (Arhitektura i urbanizam, 2024)
The article examines the architectural and urban characteristics of the residential building (type A–4), which was designed during the implementation of the Novo Naselje urban project in Novi Sad in the 1970s. The authors were architects Slavko Županski, Bora Radusinović and Radoje Cvetkov. Based on their project, three semi-open blocks of flats were built in the new urban settlement. This innovative multi-family housing project won the Vojvodina Borba Award for Architecture in 1979. Since the first Vojvodina Borba award in 1975, there have been nominations and awards for the construction of various typologies, confirming the importance of architecture for the community. The award-winning and nominated architecture in Vojvodina is represented by the unique design approach of each author, expressed in the structure and aesthetics of lowland modernism, where the culture of living and the culture of building are equally sublimated, developed in a positive relationship with the environment (urban and natural). In the area of Novo Naselje, the urban plan was intended to enable the improvement of living conditions by building better apartments (in terms of surface area and equipment) and improving the social cohesion of the population through different social groups. The architecture of the A–4 type housing studied is characterised by the development of the concept of the block in relation to the urban environment of the settlement and a study of the housing needs, which resulted in different possibilities for the organisation and use of the dwellings. The authors emphasised their intention to create houses that are lived in both inside and outside, with forms and environmental values that the tenants can identify with and live together. In all these processes, the authors sought a link between the collective housing architecture they were working on and traditional Pannonian houses.
Keywords: housing architecture; housing block; convertible apartment; housing quality; Novi Sad; „Borba“ Award for architecture